Animal Matchup: A Drag-and-Drop Interactive Game to Foster Knowledge of Animals on Android - Jazuli, Muhammad Syauqi; Rizki, Muhammad; Syaidatus Shofa Abdul Hayat, Nadiyah (Gameology and Multimedia Expert, 2025)
This study discusses the development of an interactive educational Android-based game called Animal Matchup, designed to combine entertainment with learning about the animal world. Built using the Unity platform with the C# programming language, this game presents various challenges ranging from identifying animal names, diets, to habitats through an engaging drag-and-drop mechanism. Featuring cheerful visuals, a user-friendly interface, a point and level system, as well as life indicators, the game aims to gradually enhance players’ basic biological knowledge. Initial testing showed that the game runs stably across multiple devices with responsive displays, and can motivate users to keep playing while learning. Therefore, Animal Matchup is expected to serve as an effective and enjoyable alternative learning medium for children and teenagers, while enriching science literacy related to animals and ecosystems.